Activos Exigibles Vencidos A Terceros De La Cooperativa De Ahorro Y Credito Juan Pio De Mora Oficina Caluma - Riera Morales, Maricela Juliana (2017)
The present case study deals with the demandable assets of the savings and credit cooperative Juan Pio de Mora Caluma branch. This entity is 100% dedicated to the provision of financial services and immediate support to small and large merchants, to strengthen their lucrative destiny directly and indirectly. There have been deficiencies in this item on the part of the members that form part of this economic grouping and are taking part in the services provided by the cooperative. As a main objective, the purpose of this case study is to comply with the requirements of the degree system, following the research sub lines of ICA's ACCOUNTING INFORMATION MANAGEMENT and publicize the problems that exist in the credit department of the savings and credit cooperative Juan Pio de Mora, in terms of the past due loan portfolio. In obtaining information for the development of the subject, there was not enough opening of the credit department since there are deficiencies in the delivery of the documentation of the credits granted to the partners, this is due to the staff that works in this area is not qualified in its functions.